OBSERVATION OF WATER QUALITY FOR THE CULTIVATION OF CANTANG GROUPER IN PULO PANJANG, SERANG BANTEN - Lubi Yazid Al Jazari; Saifullah Saifullah; Muh. Herjayanto (Universitas Mataram, 2026)
Water is a cultivation medium that serves as a habitat for cultivated organisms. Information regarding its quality standards is necessary for the feasibility of fish culture. Cultivated organisms will experience changes, either directly or indirectly, if the aquatic environment they inhabit is unstable. This study aims to determine the suitability of Pulo Panjang waters for Cantang grouper cultivation based on its water quality standards. In this study, a purposive sampling method was used to determine the observation stations. The research parameters observed in situ were dissolved oxygen using the Winkler method, water depth using measuring tape, water transparency using a Secchi disk, salinity using a refractometer, pH using a pH meter, temperature using a thermometer, and current velocity using the Langrangian method. Moreover, the parameters observed ex situ were nitrate using the APHA method for nitrate measurement and phosphate using the APHA method for phosphate measurement. Observations of the research parameters were carried out three times every two weeks. The results of the parameter measurements obtained were then scored and compared with those of the water suitability class. Observations show that station 1 falls into the marginally suitable category (S3) with a score of 68%, station 2 falls into the marginally suitable category (S3) with a score of 68%, and station 3 falls into the unsuitable category (N) with a score of 64%. These findings indicate that the water quality at stations 1 and 2 is suitable, and station 3 is not suitable for use in Cantang grouper cultivation activity.